It Might Be Time for Multilingual Publications in Medicine - Kaya Chakrabortty; Deepak Gupta (NMO Journal)
Non-English-language publication citations in PubMed® and their indexing in MEDLINE have not been known for producing multilingual publication citations, and this is becoming more common. The authors have explored the vastness of Japanese-language publication citations in PubMed® from Japan for publishing the results in a multilingual format. The percentage of Japanese-language publication citations in PubMed® from Japan started shooting up in 1961 to reach its zenith in 1971 at 81% before starting to plummet after 1986 to reach its rock bottom at 3% in 2022. This may be explained by the initially stagnating numbers and now decreasing numbers of Japanese-language publication citations in PubMed®, which are not able to keep up with exploding numbers of non-Japanese-language publication citations in PubMed®.